Racial Violence in ‘Action’: Police Storytelling and Narrativisation in the Inquiry of Jermaine Baker - Arthur, Carson Cole (The British journal of criminology, 2025)
Police tell stories not only to make sense of their experiences but also, as this paper argues, they tell stories to establish legal doctrines and support justifications for their decisions. Departing from police ethnography and narrative criminology, adopting a deconstructive and critical Black Studies perspective, this paper reads the narrative W80 (a London Met police firearms officer) provided in the inquiry into the death of Jermaine Baker, a 28-year-old Black man, in 2015, to examine how uncertainty was both conditional and functional in the narrative to sustain the justification of racial violence. W80’s narrative reveals how causality undergirds the law of self-defence he cited and related on. Problematizing the distinction of story and action, this paper analyses W80’s narrative for its thematic of fiction and truth. Attending to this, the paper argues the conditions of uncertainty and open-endedness of W80’s narrative reserved for racial violence to be reasoned and justified as lawful.